Effect of Soil Test Based Fertilizer Package for Yield and Economic Return of Lentil + Mustard Mixed Cropping System In Charland of Pabna (Bangladesh Agronomy Journal, 2020)
The experiment was conducted at char Sadipur the char land of Pabna during the Rabi season of 2013-14 and 2014-15 to determine appropriate fertilizer dose for enhancing production and economic return from Lentil+ Mustard mixed cropping system. The experiment was laid out in a randomized complete block design with 3 dispersed replications. Eight soil test based fertilizer packages viz.,T1: N20 P24 K20 S18 Zn2 B1.5, T2: N25 P24 K20 S18 Zn2 B1.5, T3: N25 P30 K20 S18 Zn2 B1.5, T4: N25 P24 K25 S18 Zn2 B1.5, T5: N20 P30 K25 S18 Zn2 B1.5, T6: N25 P30 K25 S18 Zn2 B1.5, T7: N15 P18 K15 S14 Zn1.5 B1kg ha-1kg ha-1 and T8: native nutrient (control) were tested for lentil + mustard mixed cropping system. Soil test based N25 P30 K25 S18 Zn2 B1.5 (T6) showed better performance on crop growth and yield of lentil and mustard in lentil+ mustard mixed cropping system in both the year. The highest lentil yield 0.70 t ha-1 in 2013-14 and 0.95 t ha-1 in 2014-15 was obtained from soil test based N25 P30 K25 S18 Zn2 B1.5 (T6). Similarly, maximum lentil equivalent yield (1233 Kg ha-1in 2013-14 and 1280Kg ha-1 in 2014-15) was also obtained from the same treatment. The maximum gross margin (Tk. 31639 ha-1 in 2013-14 and Tk. 32480 ha-1 in 2014-15) was recorded from soil test based N25 P30 K25 S18 Zn2 B1.5. So, application of soil test based fertilizer increases lentil and mustard yield as mixed crop  as well as income of the farmers.Bangladesh Agron. J. 2019, 22(1): 1-6